Decitabine combined with reduced-intensity conditioning for older patients with acute myeloid leukemia in composite complete remission undergoing allogeneic hematopoietic stem cell transplantation: a multicenter, single-arm, phase 2 trialResearch in context - Qifa Liu; Zhongli Hu; Na Xu; Yirong Jiang; Zhiping Fan; Fen Huang; Ren Lin; Hua Jin; Yunxin Zeng; Hai He; Ping Zhu; Guopan Yu; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Outcomes of older patients with acute myeloid leukemia (AML) undergoing allogeneic hematopoietic stem-cell transplantation (allo-HSCT) remain unsatisfactory. The primary objective of this trial was to establish whether decitabine combined with reduced-intensity conditioning (RIC) regimen could improve overall survival (OS) for this population in composite complete remission (CRc). Methods: We conducted a single-arm, phase 2 trial at six hospitals in China. Eligible patients were aged 60–80 years, had a diagnosis of AML, achieved CRc at transplantation, were willing to undergo the first allo-HSCT, and had an Eastern Cooperative Oncology Group performance status of 0–2. Patients received decitabine combined with RIC regimen, comprising decitabine 20 mg/m2 daily intravenously (days −9 to −7), busulfan 3.2 mg/kg daily intravenously (days −5 to −4), and fludarabine 30 mg/m2 daily intravenously (days −6 to −3). The primary endpoint was 2-year OS rate. All efficacy and safety endpoints were assessed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov (NCT03530085) and is complete. Findings: Between Jan 1, 2021 and Nov 30, 2022, 60 patients were enrolled. With a median follow-up of 35.5 months (IQR 32.5–39.2), 39 patients survived and 21 died. The 2-year OS rate was 67% (95% CI 56–80), which met the primary objective. Within 100 days post-transplantation, the most common grade 3–4 non-hematological treatment-emergent adverse events (TEAEs) were infections (22 [37%]), acute graft-versus-host disease (21 [35%]), and gastrointestinal disorders (16 [27%]). Five (8%) patients died of TEAEs, with one death treatment-related. Interpretation: Decitabine combined with RIC regimen exhibits encouraging OS and acceptable toxicity profile, which might be a suitable therapeutic option for older patients with AML. Funding: National Natural Science Foundation of China; Science and Technology Program of Guangdong Province; National Key Research and Development Program of China.